New Bioinspired Polymer Consolidants for the Oseberg Artefacts and Other Archaeological Wood - Cutajar, Michelle (2023)
The Oseberg Viking ship burial is one of the most extensive collections of Viking wooden artefacts discovered in the world. In the early 20th century, many of these artefacts were treated with alum. Today, it is known that this alum treatment was very damaging to the wood, as a significant number of the artefacts demonstrate a high degree of deterioration. The Saving Oseberg project was set up in 2014 by the Museum of Cultural History at the University of Oslo to work towards gaining understanding of the chemical composition of the alum-treated wood and establishing novel conservation treatments. Current studies on the state of the Oseberg collection prove that the artefacts are undergoing continuous degradation.